Sequence Diversity of Neisseria meningitidis 16S rRNA Genes and Use of 16S rRNA Gene Sequencing as a Molecular Subtyping Tool - Sacchi, Claudio T. (American Society for Microbiology (ASM), 2002)
We investigated the diversity of the primary sequences of 16S rRNA genes among Neisseria meningitidis strains (Men) and evaluated the use of this approach as a molecular subtyping tool. We aligned and compared a 1,417-bp fragment of the 16S rRNA gene from 264 Men strains of serogroups A, B, C, and Y (MenA, MenB, MenC, and MenY, respectively) isolated throughout the world over a 30-year period. Thirty-one positions of difference were found among 49 16S types: differences between types ranged from 1 to 14 positions (0.07 to 0.95%). 16S types and serogroups were highly associated; only 3 out 49 16S types were shared by two or more serogroups. We have identified 16S types that are exclusively associated with strains of certain hypervirulent clones: 16S type 5 with MenA subgroup III, 16S type 4 with the MenB electrophoretic type 5 (ET-5) complex, and 16S types 12 and 13 with MenC of the ET-37 complex. For MenC strains, 16S sequencing provided the highest sensitivity and specificity and the best overall association with the outbreak-related versus sporadic isolates when compared with pulsed-field gel electrophoresis, multilocus enzyme electrophoresis, and multilocus sequence typing. We demonstrated for the first time an unexpected diversity among 16S rRNA genes of Men strains, identified 16S types associated with well-defined hypervirulent clones, and showed the potential of this approach to rapidly identify virulent strains associated with outbreaks and/or an increased incidence of sporadic disease.